2020
DOI: 10.1016/j.wroa.2020.100071
|View full text |Cite
|
Sign up to set email alerts
|

CrAssphage for fecal source tracking in Chile: Covariation with norovirus, HF183, and bacterial indicators

Abstract: Anthropogenic fecal pollution in urban waterbodies can promote the spread of waterborne disease. The objective of this study was to test crAssphage, a novel viral human fecal marker not previously applied for fecal source tracking in Latin America, as a fecal pollution marker in an urban river in Chile. Human fecal markers crAssphage CPQ_064 and Bacteroides HF183, the human pathogen norovirus GII, and culturable fecal indicator bacteria (FIB) were quantified at six locations spanning rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…However, when a high residual concentration of PAA was maintained in the washing tank, the counts of total and F-specific RNA coliphages decreased one log with respect to the prewashing counts, with no differences between total and F-specific RNA coliphages (Table 2). Previous studies reported for MNV, a norovirus surrogate, that lower doses of PAA (40,80, and 120 ppm) could inactivate about 3.8 log MNV in artificially inoculated PW from the strawberry industry [27]. However, the conditions used in the mentioned study were very different from those of the industry.…”
Section: Occurrence Of Coliphages and Human Enteric Viruses In Process Watermentioning
confidence: 83%
See 1 more Smart Citation
“…However, when a high residual concentration of PAA was maintained in the washing tank, the counts of total and F-specific RNA coliphages decreased one log with respect to the prewashing counts, with no differences between total and F-specific RNA coliphages (Table 2). Previous studies reported for MNV, a norovirus surrogate, that lower doses of PAA (40,80, and 120 ppm) could inactivate about 3.8 log MNV in artificially inoculated PW from the strawberry industry [27]. However, the conditions used in the mentioned study were very different from those of the industry.…”
Section: Occurrence Of Coliphages and Human Enteric Viruses In Process Watermentioning
confidence: 83%
“…Therefore, based on the observed data, crAssphage cannot be suggested as a good indicator for the presence of enteric viruses in PW. Recent studies have shown a correlation between crAssphage and human viral pathogens in other water matrices such as wastewaters [33][34][35][36][37][38], sludge [39], and other fecal polluted waters [40]. Altogether, these and our results suggest that crAssphage correlates with the occurrence of human pathogenic enteric viruses in water samples with moderate viral contamination (e.g., effluent waters), but not in severely or poorly contaminated waters (e.g., surface, river, influent, seawater, or process water).…”
Section: Occurrence Of Coliphages and Human Enteric Viruses In Process Watermentioning
confidence: 99%
“…Indicators of fecal contributions from wastewater have been increasingly advocated as a means to normalize SARS-CoV-2 RNA concentration estimates according to fecal loading in the wastewater sample that might enable improved detection of temporal trends within a given community. Common viral indicators used for this purpose include the Pepper Mild Mottle virus (PMMoV) ( Graham et al., 2020 ; Jafferali et al., 2020 ), crAssphage ( Green et al., 2020 ; Jennings et al., 2020 ; Stachler et al., 2017 ), or other human fecal specific bacteriophages or biomarkers. Chemical substances such as the excretory product creatinine and the calorie-free sugar substitute acesulfame ( Lin et al., 2019 ), or physically-based wastewater volumetric flow rates might also be used to normalize SARS-CoV-2 RNA concentration estimates.…”
Section: Discussionmentioning
confidence: 99%
“…However, whilst fecal indicator bacteria were detected and enumerated in country in this cross-sectional study of 60 villages in India, the quantitative PCR assays for the MST indicators (BacUni, BacHum and BacCow, BacCan) were performed on samples that were stored on ice for up to 2 months, prior to being sent to the United States for analysis. Similarly, molecular-based MST studies that have been conducted in a variety of rural and urban low-income settings, including Kenya, Mozambique, Bangladesh, and Chile, relied on shipping the samples to a lab in a high-income country to perform the analyses ( Jenkins et al, 2009 ; Harris et al, 2016 ; Bauza et al, 2019 ; Fuhrmeister et al, 2019 , 2020 ; Holcomb et al, 2020 ; Jennings et al, 2020 ). The findings of this Kolkata study are significant as they demonstrate that a phage-based MST assay offers a low-cost, rapid (18 h) MST approach that laboratories in the region can employ to elucidate human and non-human fecal contamination sources and transmission pathways in complex urban environments such as those present in Kolkata, India.…”
Section: Discussionmentioning
confidence: 99%
“…This includes a range of non-molecular approaches, such as those involving the detection of specific bacteriophages ( Puig et al, 1999 ; Payan et al, 2005 ; Ebdon et al, 2007 , 2012 ; Wicki et al, 2011 ; Jofre et al, 2014 ; McMinn et al, 2014 ; Diston and Wicki, 2015 ; Dias et al, 2018 ) and molecular-based markers (e.g., Bacteroidales and crAssphage qPCR markers) which have shown considerable promise as MST markers ( Reischer et al, 2013 ; Stachler et al, 2017 ; Ahmed et al, 2018a , b ; Mayer et al, 2018 ). However, despite the fact that studies of pollution sources have been conducted in a range of rural and urban low-income settings (e.g., Kenya, India, Mozambique, Bangladesh, Chile) most MST studies have involved shipping samples to laboratories in high-income countries for analysis ( Jenkins et al, 2009 ; Odagiri et al, 2015 , 2016 ; Harris et al, 2016 ; Bauza et al, 2019 ; Fuhrmeister et al, 2019 , 2020 ; Holcomb et al, 2020 ; Jennings et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%